And thus became man and world - Z'graggen, John Anton, 1932- (The Pentland Press, 1992)
"In this book Fr. John Z'graggen gives a fascinating presentation of a variety of myths of creation as made up by the peoples of the Madang Province, Papua New Guinea, in the South Pacific."